Limitation Of Religious Spiritual Values And Increasing Spiritual Decay During The Soviet Government (Eurasian Journal of Humanities and Social Sciences, 2024)
This article analyzes the nature of the policy towards religion during the time of the Soviet government and the reasons for the destruction of national and religious values